(untitled) (Journal of Economic Research & Business Administration, 2021)
This article provides an overview of the state of medium and small businesses in the context of the COVID-19 pandemic. At the end of February 2020, right before European countries instituted various forms of lockdowns, The Lancet published a review of 24 studies documenting the psychological impact of quarantine (“restricting the movement of people who are potentially susceptible to contagious disease”). The findings provide insight into what is happening in hundreds of millions of businesses around the world. In our country, private medical organizations as small and medium-sized businesses are also among the economic organizations whose activities were restricted by quarantine, despite the fact that they belong to the healthcare system. A review of the activities of small and medium-sized businesses in the healthcare system (the number of employees is up to 250 people) was carried out in the context of the COVID-19 pandemic. Since infectious diseases and provisional hospitals ensured their work in emergencies and within the framework of the guaranteed volume of medical care, private clinics were not involved. Some clinics provided paid services for the diagnosis of coronavirus (PCR studies, computed tomography of the lungs, radiography of the lungs) and partially provided medical services to a small part of the population. In this regard, the activities of these organizations were terminated or some types of services were reduced, and the working part – medical workers became a vulnerable part, which the employer was not able to compensate for the losses. In this regard, both employers and employees are affected. Key words: COVID-19, small and medium enterprises, risks, digital transformation and sustainability.